Development and validation of a liquid chromatography with tandem mass spectrometry method for the quantification of vitisin B in rat plasma and urine. Issue 11 (27th April 2015) - Choi, Woong‐Kee; Yoon, Kee Dong; Lee, Joeng Kee; Park, Jung Bae; Heo, Tae‐Hwe; Lee, Choongho; Bae, Soo Kyung
<x xml:space="preserve">Abstract</x> A new, rapid, and sensitive liquid chromatography with tandem mass spectrometry method was developed for the determination of vitisin B and validated in rat plasma and urine using carbamazepine as an internal standard. The plasma (0.05 mL) or urine (0.2 mL) samples were extracted by liquid–liquid extraction with ethyl acetate and separated on an Eclipse Plus C18 column (100 × 4.6 mm, 3.5 μm) with a mobile phase consisting of acetonitrile and 0.1% formic acid water (60:40, v/v) at a flow rate of 0.7 mL/min. Detection and quantification were performed by mass spectrometry in selected reaction‐monitoring mode with positive electrospray ionization. The calibration curves were recovered over the concentration ranges of 10−5000 ng/mL (correlation coefficients, r≥0.9833) in plasma and 5−2500 ng/mL (r≥0.9977) in urine, respectively. All validation data, including the specificity, precision, accuracy, recovery, and stability, conformed to the acceptance requirements. No matrix effects were observed. The developed method was successfully applied to pharmacokinetic studies of vitisin B following intravenous administration of 0.5 and 1 mg/kg and intraperitoneal injection of 5, 10, and 25 mg/kg to rats. This is the first report on the pharmacokinetic properties of vitisin B. The results provide a meaningful basis to evaluate preclinical or clinical applications of vitisin B.